2013
DOI: 10.1007/s11130-013-0393-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition, Antioxidant and Enzyme Inhibitory Activities of Eryngium bornmuelleri leaf

Abstract: Eryngium bornmuelleri Nab. (Tusî) is an endemic botanical from the Eastern Anatolia region of Turkey traditionally used for preparation of herbal tea. Within this study, phenolic composition, antioxidant capacities and inhibitory activities towards selected digestive enzymes of E. bornmuelleri leaf were investigated. Sequential extracts, obtained by extraction of plant tissue by ethanol, acetone and water exhibited pronounced antioxidant capacities and in a dose-dependent manner suppressed the metabolic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…[313233] Additionally, the efficacy of phenolic acids, namely caffeic-, rosmarinic-, and ferulic acids, as PL inhibitors are well described. [3435] In effect, the results of the present study indicate that the PL inhibitory efficacy of A. hygrophilum may be attributable to their multiple phenolic components acting additively or synergistically. [36]…”
Section: Resultsmentioning
confidence: 73%
“…[313233] Additionally, the efficacy of phenolic acids, namely caffeic-, rosmarinic-, and ferulic acids, as PL inhibitors are well described. [3435] In effect, the results of the present study indicate that the PL inhibitory efficacy of A. hygrophilum may be attributable to their multiple phenolic components acting additively or synergistically. [36]…”
Section: Resultsmentioning
confidence: 73%
“…In addition, Dalar et al [5] have suggested that rutin, quercetin, luteolin and caffeic acid obtained from E. bornmuelleri leaf extract may be responsible for their antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also observed significantly weaker inhibitory activity of plant extract as well as pure phenolic compounds against pancreatic lipase than that of orlistat [21][22][23]. For example, the IC 50 values for some Mediterranean dietary plants ranged from 0.99 to > 2.5 mg/ml while orlistat showed the IC 50 value of 0.018 mg/ml [23]. Cha et al [22] noted that (−)-epigallocatechin gallate showed the anti-lipase activity similar to that of orlistat with IC 50 =1.8 and 1.2 μM, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The total phenolic content in chokeberry was 1.04 %, while other fruits contained under 0.35 % of phenolic compounds (Table 4). Other authors also observed significantly weaker inhibitory activity of plant extract as well as pure phenolic compounds against pancreatic lipase than that of orlistat [21][22][23]. For example, the IC 50 values for some Mediterranean dietary plants ranged from 0.99 to > 2.5 mg/ml while orlistat showed the IC 50 value of 0.018 mg/ml [23].…”
Section: Resultsmentioning
confidence: 96%